ANALISIS KEBIJAKAN PENGUATAN LEMBAGA KEUANGAN SYARIAH: STUDI PERBANDINGAN INSTITUSI EKONOMI ISLAM DI UEA DAN SERBIA - Siti Maghfiroh; Naufal Luthfi Alifa (WELFARE: Journal of Islamic Economics and Finance, 2026)
The purpose of this study is to compare the policy direction and development of Islamic economic institutions (IEC) between the United Arab Emirates (UAE), a predominantly Muslim-majority country that is an international Islamic financial center, and Serbia, a Muslim-minority country in Southeastern Europe that offers new opportunities for IEC development. This study uses a descriptive qualitative approach through library research and comparative policy analysis. This study shows that the UAE can implement targeted and centralized regulations, reinforced by government support through institutions such as the Dubai Islamic Economy Development Center (DIEDC). This policy has successfully encouraged an increase in Islamic financial assets and strengthened its market position in several sectors. On the other hand, Serbia still faces structural obstacles, including low public understanding, the absence of adequate Sharia regulations, and limited retail financial products, despite the existence of Islamic banking institutions focused on corporate financing. The results of this comparison offer important lessons for Indonesia regarding the need to strengthen centralized regulations while increasing public literacy in a multicultural context.